Back Cover, Volume 2, Number 1, January 2023. Issue 1 (18th January 2023) - Chang, Wei; Luo, Kai; Wang, Pengtao; Abdulshaheed, Ahmed A.; Li, Chen
Abstract : Back Cover : The cover image is based on the Research Article Sustainble dropwise condensation enabled ultraefficient heat pipes by Chang et al. The combination of hydrophobic condenser with sustained DWC and nano‐engineered evaporator in grooved heat pipes can sufficiently decrease both the thermal resistance of condensation and evaporation simultaneously. Up to 82.3% reduction of the total thermal resistance has been realized. An ultrahigh k eff of ~ 140 kW/(m·K), which is 5.17 times higher than that of traditional groove heat pipes, has been achieved. (DOI: 10.1002/dro2.43 )